The effect of macrocysts for Sarcocystis spp. in muscular tissue of water buffaloes (Bubalus buballs) - Huda Ghanim Dakhil ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
Sarcocystosis in water buffalo is caused by eating of contaminated vegetables or water with sporocysts of Sarcocystis spp. it’s forming two types of sarcocysts are macrocysts or microcysts in their muscles , The aim of current study is to detect effect of macrocysts on the muscular tissue of infected water buffaloes . Histological examination carried out on infected oesophageal muscle of five , more than four years water buffaloes. The histological examination was showed presence of inflammation , hypertrophy and necrosis in the affected muscle tissue , addition to loss of the nuclei in the muscle cells that containing the macrocysts of sarcocystis spp. This is the first study for Histological effect of macroscopic Sarcocystis spp. infecting muscles of Iraqi water buffaloes .